In it together: A qualitative evaluation of participant experiences of a 10-week, group-based, workplace HIIT program for insufficiently active adults - Kinnafick, F.; Thogersen-Ntoumani, Cecilie; Shepherd, S.; Wilson, O.; Wagenmakers, A.; Shaw, C. (Human Kinetics, 2018)
Using guidance from the reach, efficacy, adoption, implementation, and maintenance evaluation framework, we aimed to qualitatively evaluate the participant experiences of a workplace high-intensity interval training (HIIT) intervention. Twelve previously insufficiently active individuals (four males and eight females) were interviewed once as part of three focus groups. Perceptions of program satisfaction, barriers to and facilitators of adherence, and persistence to exercise were explored. HIIT initiates interest because of its novelty, provides a sense of accomplishment, and overcomes the barriers of perceived lack of time. The feeling of relatedness between the participants can attenuate negative unpleasant responses during the HIIT sessions. HIIT, in this workplace setting, is an acceptable intervention for physically inactive adults. However, participants were reluctant to maintain the same mode of exercise, believing that HIIT sessions were for the very fit.